Industry analysis to guide the asset strategy of the human nutrition and health premix business of Company XYZ - Cooke, Jamie S. (Kansas State University, 2017)
Company XYZ is a global manufacturer of human nutrition & health (HNH) premixes. They operate globally through 14 manufacturing sites. HNH premix North America manages a network of three production facilities plus several warehouses on the east and west coasts of the United States. The purpose of this thesis is to provide insights for informing the asset strategy for the human nutrition and health premix business of Company XYZ focusing on the analysis of competitive forces and market drivers for the herbs and botanicals segment. Specifically the thesis aims to achieve the following three objectives: 1) identify potential supply chain bottlenecks and capacity constraints by mapping out the supply chain and examining the production flow, the installed capacity, and current asset strategy; 2) identify key market drivers and related industry trends by assessing the competitive forces and change forces affecting the industry growth rate; 3) present synthesis of strategic issues and strategy recommendation for asset allocation strategy. The analysis involves examination of the supply chain logistical flows for raw materials used in current production of blends and premixes as well as the supply chain for herbs and botanicals. It also includes the assessment of current production capacity by providing a detailed overview of production facilities, blending equipment, production lines and geographical coverage. The aim is to assess the existing procurement capabilities and to identify potential bottlenecks that may constrain the supply chain flow as the demand for HNH premixes grow. The industry analysis was undertaken to better understand the outlook for the premix industry and the factors driving and impeding the growth in the herbs and botanicals sector. The current premix competitive environment was evaluated for the food & beverage as well as dietary supplement sectors. In addition to calculating the industry’s concentration and Herfindahl-Hirschman index (HHI), Porter’s Five Forces framework was used to analyze the intensity of competitive forces in the industry and the attractiveness of the HNH premix industry as the demand for premixes in that segment continues its growth trajectory. The qualitative assessment of the industry structure and competitive forces was conducted using data from interviews with experts designed and conducted in the fall of 2016. The results indicate that the current asset footprint, procurement base, and supply chain capabilities of Company XYZ will allow it to position itself as a leading supplier for the growing HNH nutrition segment. In addition, the results indicate that given the high-value low-volume nature of herbs and botanical blends there are no significant strategic advantages to be gained from changes in geographic asset footprint. However, these results do not account for actual production costs and overheads at each location since the analysis did not include a financial assessment. The results from the analysis of socio-economic trends illustrate that moving forward the companies in the dietary supplement sector focused on applications that support brain and cognitive functioning will account for the largest increase in demand for herbs and botanical blends. It was recognized that Company XYZ currently finds itself in a “red ocean” where it competes over market share in a slow-growth and highly competitive industry. Two potential strategies that will help transition a company into a “blue ocean” – a high growth and low-rivalry environment involve: i) taking over customers’ in-house blending activities by offering a better value proposition through Company XYZ’s economies of scale, superior quality standards, and blending capabilities; and ii) enhancing diversification into the herbs and botanicals segment of the HNH premix industry focusing on brain health applications.
Keywords: Premix; Asset strategy; Industry analysis; Supply chain; Herbs and botanicals; Food and beverage